2023
DOI: 10.1186/s12875-023-02088-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians' perspectives and challenges on managing multimorbidity for patients with dementia: a Japan–Michigan qualitative comparative study

Abstract: Background Multimorbidity management can be extremely challenging in patients with dementia. This study aimed to elucidate the approaches of primary care physicians in Japan and the United States (US) in managing multimorbidity for patients with dementia and discuss the challenges involved. Methods This qualitative study was conducted through one-on-one semi-structured interviews among primary care physicians, 24 each from Japan and Michigan, US. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Despite the increased prevalence of ADRD and the severity of MCC in people with ADRD, current clinical practice guidelines for MCC have yet to address priority changes for people with ADRD. 25 , 26 , 27 Our study demonstrated the potential of utilizing AI/ML approaches to unravel the complex MCC patterns among people with ADRD adjusted by the theoretical syndemic framework proposed by Dunn et al. 17 Our work provided a useful clinical tool to help early identify MCC that has not happened (or developing) based on MCC and syndemic factors an ADRD patient has had, by providing a list of MCC that might happen in the next visit.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite the increased prevalence of ADRD and the severity of MCC in people with ADRD, current clinical practice guidelines for MCC have yet to address priority changes for people with ADRD. 25 , 26 , 27 Our study demonstrated the potential of utilizing AI/ML approaches to unravel the complex MCC patterns among people with ADRD adjusted by the theoretical syndemic framework proposed by Dunn et al. 17 Our work provided a useful clinical tool to help early identify MCC that has not happened (or developing) based on MCC and syndemic factors an ADRD patient has had, by providing a list of MCC that might happen in the next visit.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the increased prevalence of ADRD and the severity of MCC in people with ADRD, current clinical practice guidelines for MCC have yet to address priority changes for people with ADRD. [25][26][27] Our study demonstrated the potential of utilizing AI/ML approaches to unravel the complex MCC patterns among people with ADRD adjusted by the theoretical syndemic framework proposed by Dunn et al 17…”
Section: Discussionmentioning
confidence: 91%